Tubos em compósito de epóxi reforçado com fibra de vidro produzidos pelo processo de enrolamento filamentar para aplicação na indústria petroquímica - Guiguer, Elton Landgraf (2021)
This work is focused on the production and mechanical performance evaluation of filament-wound flat plates and pipes using different composite compositions of three distinct commercial high glass transition epoxy resins reinforced with glass fiber (GRE) in order to verify their potential usage in the petrochemical industry. The evaluation included measurements of the glass transition temperature, Tg, of the epoxy matrix resins through Dynamic Mechanical Analysis (DMA) and by Differential Scanning Calorimetry (DSC) for the produced GRE composites tubes. Also, the mechanical performance of these different GRE composites was analyzed through mechanical tensile, shear, flexural and impact strength properties using current materials testing standards. The mechanical properties results were compared with their theoretical values calculated using the simple rule of mixtures equations. Furthermore, a pipe was designed using the classical laminate theory analysis and samples were produced and tested according to the API 15 burst test standard. The evaluation of fiber/resin interfacial compatibility was investigated by scanning electronic microscopy analysis in order to correlate the interfacial adhesion with the obtained mechanical properties. The experimental results are close to the foresee values for Tg and mechanical results, in the second case considering the coupons production process limitations. This screening project showed potential usage glass fiber reinforced epoxy pipes for oil extraction production columns in the undersea pre-salt regions. Evidently, it is necessary to further investigate more deeply into the subject before an installation of such GRE tubes are reliable enough for use under the severe operation conditions in the short, medium and long term.